THE STRATEGIES TO IMPROVE SERVICE QUALITY THROUGH DIGITALIZATION OF JCONNECT MOBILE BANKING AT BPD EAST JAVA: STRATEGI PENINGKATAN KUALITAS PELAYANAN MELALUI DIGITALISASI MOBILE BANKING JCONNECT PADA BPD JAWA TIMUR - Dikril Faizun; Saiful Bakhri; Sultan Hasanudin (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
JConnect Mobile Banking is one of the innovative products and services of Bank Jatim based on e-channel, which allows the Bank to provide services to its customers through mobile phones using mobile applications on android and iOS platforms that use internet data packages in transactions. This research is descriptive research that aims to collect actual information in detail that explains the Strategy for Improving Service Quality Through Digitalization of Mobile Banking Jconnect at BPD East Java. Mobile banking via cell phones is very easy to understand, does not incur additional costs, and has security features that ensure banking transactions are carried out safely and securely.